2017
DOI: 10.1136/neurintsurg-2017-013532
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet pretreatment and outcomes following mechanical thrombectomy for emergent large vessel occlusion strokes

Abstract: APT pretreatment does not increase the risk of sICH and may independently improve the odds of SR in patients with ELVO treated with MT. The former association appears to be modified by IVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 32 publications
3
38
3
Order By: Relevance
“…Stroke severity at hospital admission was documented using National Institutes of Health Stroke Scale (NIHSS) scores by certified vascular neurologists. Baseline characteristics, including demographics, vascular risk factors, history of prior stroke, admission NIHSS scores, admission Alberta Stroke Program Early CT Score (ASPECTS), pretreatment with IVT, admission serum glucose, admission systolic blood pressure and diastolic blood pressure levels, occlusion site (anterior vs posterior circulation occlusion), were recorded as previously described 14. Collateral scores were reported in a dichotomized fashion (good vs poor collaterals) for anterior circulation ELVO using a methodology that has been shown to predict clinical outcome 15.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke severity at hospital admission was documented using National Institutes of Health Stroke Scale (NIHSS) scores by certified vascular neurologists. Baseline characteristics, including demographics, vascular risk factors, history of prior stroke, admission NIHSS scores, admission Alberta Stroke Program Early CT Score (ASPECTS), pretreatment with IVT, admission serum glucose, admission systolic blood pressure and diastolic blood pressure levels, occlusion site (anterior vs posterior circulation occlusion), were recorded as previously described 14. Collateral scores were reported in a dichotomized fashion (good vs poor collaterals) for anterior circulation ELVO using a methodology that has been shown to predict clinical outcome 15.…”
Section: Methodsmentioning
confidence: 99%
“…Functional independence (FI) was defined as mRS scores of 0–2 at 3 months. Endovascular specialists grading the degree of reperfusion at the end of MT and vascular neurologists assessing NIHSS and mRS scores were unaware of the purposes of the study and performed treatments and assessments as part of their clinical duties 14…”
Section: Methodsmentioning
confidence: 99%
“…Seven studies were identified in which tandem lesions were investigated, and one RCT investigating the effectiveness of MT was identified, in which periprocedural antithrombotics were used. A total of 19 articles met the selection criteria and were included in the review (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Study Selectionmentioning
confidence: 99%
“…Three studies reported unadjusted effect estimates of antiplatelet use on mortality and functional independence (22,32,39). The relative effect on mortality was neutral in two studies (OR, 0.75; 95% CI, 0.34-1.67, and OR, 0.97; 95% CI, 0.50-1.85) (22,39) and higher in the other (OR, 2.46; 95% CI, 1.27-4.76) (32), when antiplatelet agents were used. In all studies, the effect on functional independency was neutral (OR, 0.61; 95% CI, 0.32-1.17, and OR, 0.54; 95% CI, 0.28-1.05, and OR, 1.11; 95% CI, 0.63-1.97).…”
Section: Thrombectomy and Antiplatelet Usementioning
confidence: 99%
See 1 more Smart Citation